Susceptibilidade do piloro de Bombyx mori (Lepidoptera, bombycidae) ao bombyx mori multiple nucleopolyhedrovirus - Baggio, Mayarha Patricia Dequigiovanni (2013)
Bombyx mori multiple nucleopolyedrovirus (BmMNPV) is an entomopathogenic virus of the Baculoviridaefamily, genera Alphabaculovirus, which infects the silkworm (Bombyx Mori) and causes nuclear polyhedrosis disease. This virus is poliorganotrophic and a series of tissues are known as targets; however, literature does not present information in regards to the pylorus, segment of the hindgut, present in the transition with the midgut and responsible for regulating the passage of food towards the ileum. The organ is, thus, of fundamental importance in the ending of the digestive process, affecting the insect s metabolic balance and, the present study sought to analyze its susceptibility and cytopathology in regards to BmMNPV, geographic isolate of Paraná, Brazil. Moreover, due to the complexity of this segment, its general morphology will also be analyzed. In order to do so, hybrid B.mori caterpillars at 5º instar were inoculated experimentally with a viral suspension of BmMNPV. On different day post-inoculation (dpi), from 2º to 9ºdpi, segments of the intestine, containing the pylorus, with its subdivisions (posterior interstitial ring, pyloric cone and pyloric valve), were dissected, following the routine histological processing for paraffin wax blockage and dyes in haematoxylin and eosin, for general morphology analysis, and in modified Azan staining, for cytopathology. Segments also processed to form scanning electronic microscope for analized of morphological details. So the pylorus general morphology the caterpillars of B. mori, was similar to that observed in other insects. The cytopathology showed that the anterior area of the posterior interstitial ring is a secondary target of infection for the BmMNPV, after 5º dpi, and its infectious cycle is similar to that described in literature. In the hypertrophic nucleus one there the formation of viroplasm, place for production of enveloped nucleocapsids or virions, following the formation and development of the polyhedra. Later on, cytolysis occurred, promoting the liberation of polyhedra and the spreading of the disease, mainly in the B. mori creation sheds. The posterior area of the posterior interstitial ring, the pyloric cone and the pyloric valve did not reveal any traces of infection by BmMNPV and, thus, resistance mechanisms involving genetic factors could be acting. The knowledge obtained from this work will contribute in the establishment of the infectious cycle of this important entomopathogenic virus, which may lead to an epizootic that can negatively affect the whole productive chain of silk